2020
DOI: 10.1002/aur.2452
|View full text |Cite
|
Sign up to set email alerts
|

Priors Bias Perceptual Decisions in Autism, But Are Less Flexibly Adjusted to the Context

Abstract: According to the predictive coding framework, percepts emerge from combinations of sensory input and prior knowledge, whose relative contributions depend on their reliability. Recent predictive coding theories suggest that Autism Spectrum Disorder (ASD) could be characterized by an atypical weighting of priors. Here, we assessed whether individuals with ASD can flexibly adjust the weight (precision) of the prior to the context. Thirty‐one neurotypical adults (NT) and 26 adults with ASD participated in a visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…priors learned over shorter time scales) gave more heterogeneous results in ASD. For instance, low-level perceptual tasks in autistic adults showed slower prior learning in ASD [ 21 ] or more inflexible priors [ 22 ]. Results of associative learning tasks in ASD often depend on context.…”
Section: Introductionmentioning
confidence: 99%
“…priors learned over shorter time scales) gave more heterogeneous results in ASD. For instance, low-level perceptual tasks in autistic adults showed slower prior learning in ASD [ 21 ] or more inflexible priors [ 22 ]. Results of associative learning tasks in ASD often depend on context.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility was suggested by previous concepts and studies. 11,19,31,36 Because inflexibility has been defined inconsistently in the context of Bayesian perception, the findings might also be explained by other causes, 36,37 as discussed by some authors. 19…”
Section: Discussionmentioning
confidence: 93%
“…(i) many studies did not compare the relative plausibility of the different hypotheses but tested a single one, (ii) some studies did not examine individuals with a clinical diagnosis of ASD, but autistic traits in the general population, 26,29,31 and when diagnosed individuals were investigated, (iii) sample sizes were mostly small, ranging from N=14 to N=26 in most studies, 19,22,24,25,28,[31][32][33]36,37,44 with few exceptions. 23,27,34 In the current study, we tried to address these issues and designed a set of experiments to systematically test the different hypotheses in a larger clinical sample (47 adults diagnosed with ASD and 50 matched controls).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An imbalance in the weight attributed to sensory input and predictions in autism (Brock, 2012;Pellicano & Burr, 2012) could lead to high precision of prediction errors (Van de Cruys et al, 2014), meaning that predictions would not be flexibly adjusted according to the context (Sapey-Triomphe et al, 2021;Van de Cruys et al, 2014). In line with this hypothesis, Sapey-Triomphe et al (2021) found that autistic adults , unlike TD participants, constructed priors but did not flexibly modulate them according to the context during a low-level discrimination task. These findings might generalize to different tasks or situations requiring flexibility and could partly explain flexibility difficulties in autism and why these difficulties appear in unpredictable situations.…”
Section: Introductionmentioning
confidence: 99%